Review of Islamic Law and Positive Law Regarding Legal Protection for Children as Offenders of Crime: Case Studies in West Java - Zulbaidah; Neng Yani Nurhayani; Dewi Sulastri (International Journal of Science and Society, 2023)
This study aims to reveal the development of children as perpetrators of crimes in the West Java region, and also to analyze the legal protection for children who are involved in criminal acts, both from the perspective of Islamic law and positive law. In addition, this study identifies obstacles in educating children who are involved in criminal behavior. In this study, a combined approach method of normative and empirical research was used. The normative approach is carried out by investigating data and facts through literature studies and comparisons of legal literature, including derivative legal products, as well as analysis of the relevance of legal views to the object of research. On the other hand, the empirical approach involves public testing and direct data search (field research) from related parties, including Center for Integrated Service for the Empowerment of Women and Children “Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak” (P2TP2A) and Legal Aid Institutions. The results of the research show that in the case of children as perpetrators of criminal acts, the restorative justice approach is a relevant concept. Limitations of thinking and careful consideration in children are the main factors that support the choice of this approach. Thus, in providing criminal responsibility for children, it is important to consider their development and best interests for their future. Incorrect handling can have a damaging impact on future generations. This is because children are assets as well as successors to the nation and the ideals of the state. Meanwhile, the obstacles faced in educating children who commit criminal acts include, first, sometimes the perpetrator's parents completely surrender to the Social Service, so this is what then becomes an obstacle in providing assistance. The second is the budgetary aspect, in some cases such as harassment, regarding the post-mortem fee, parents sometimes hand it over in full, not to mention if there are additional costs, the Social Service will automatically bear it. The third obstacle is the cooperation that is established with Legal Aid Institutions “Lembaga Bantuan Hukum” (LBH) which demand payment, while social services are government agencies whose allocation has been determined.